Optimization of Oyster Mushroom Business Development Through SWOT and QSPM - Iman Nurjaman; Sandi Sandi; Bramantiyo Eko Putro (Universitas Serang Raya, 2025)
This research was conducted at CV. Asa Agro Corporation, Cianjur, West Java, Indonesia, is a region with optimal climatic conditions for oyster mushroom cultivation. Despite the sector's potential, challenges such as product quality instability and fluctuating productivity hinder business growth. This research employs an integrated SWOT analysis strengthened by IFAS, EFAS matrices, and Quantitative Strategic Planning Matrix (QSPM) to systematically identify critical internal and external factors and formulate prioritized strategies. Unlike previous studies that predominantly rely on descriptive SWOT frameworks, this research integrates quantitative weightings and empirical prioritization through QSPM, thereby addressing a significant methodological gap in mushroom agribusiness decision-support literature and enhancing objectivity in managerial strategy formulation. Data were gathered through structured questionnaires, field observations, and secondary reports from 30 purposively selected respondents. This analysis revealed strong internal factors, including strategic location and superior spawn quality (IFAS score 2.95). In addition, there are several significant external opportunities, such as increasing consumer health awareness and government support (EFAS score 2.78). The positive relationship between time and production (r = 0.95; p < 0.05) suggests a trend of steady expansion from 2020 to 2024. This quantitative integration allows for measurable improvement in strategic decision-making precision, with QSPM scores providing clear prioritization metrics (SO strategy: 3.2; WO: 3.1; ST: 3.0; WT: 2.6). This study offers SO strategies with a QSPM score of 3.2 by utilizing strategic priorities and quantitative approaches to optimize long-term sustainable competitive advantages in the oyster mushroom agricultural sector.